GALOH AJANG - Asrul Asshadi, Mohamad Morni; Alexander, Chelum (UNIMAS Publisher, 2024)
This artwork captures the artist's profound fascination with and exploration of Songket motifs through semiotic methods. Songket serves as the canvas for conveying cultural narratives and symbolism. The precisely crafted and arranged motifs on Songket form a visual language steeped in tradition yet relevant in the contemporary context. The artwork encourages viewers to decipher the concealed meanings and tales woven into Songket, forging a connection between the past and the present while honoring its cultural importance. Ultimately, it serves as a tribute to the enduring legacy and beauty of Songket.